Management of selected waste generated during cable production - Studziński, Waldemar; Gackowska, Alicja; Dadzibóg, Michał (Environmental science and pollution research international, 2024)
The subject of the research was the recovery of raw materials from waste generated in the production of cable insulation and the management of aluminum sludge. It was found that 49% (w/w) acetophenone, 6.8% (w/w) α-methylstyrene, and 17.2% (w/w) cumyl alcohol can be recovered from waste with a loss on ignition of 95% and used in various industries. A gas chromatograph equipped with a mass spectrometry detector was used to identify the recovered compounds. A waste distillation process was proposed to remove the water layer and obtain a concentrated acetophenone fraction. A method of neutralizing the water fraction and distillation residues is presented. The proposed waste management method is an alternative method to the currently used thermal transformation method. In turn, aluminum sludge was used to produce aluminum sulfate, which was used in the plant’s sewage treatment plant as a coagulant. The effect of this action was a reduction of 67% in the content of total iron, 60% of trivalent iron, and 32% of chemical oxygen demand. The above-mentioned examples of waste management are part of a closed-loop waste management strategy.